2016
DOI: 10.1007/s00253-016-7521-9
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic engineering of enhanced glycerol-3-phosphate synthesis to increase lipid production in Synechocystis sp. PCC 6803

Abstract: With the growing attention to global warming and energy sustainability, biosynthesis of lipids by photosynthetic microorganisms has attracted more interest for the production of renewable transportation fuels. Recently, the cyanobacterium Synechocystis sp. PCC 6803 has been widely used for biofuel production through metabolic engineering because of its efficient photosynthesis and well-developed genetic tools. In lipid biosynthesis, glycerol-3-phosphate (G3P) is a key node for both CO2 fixation and lipid metab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…However, the previous study suggested that overexpression of RuBisCO driven under psbA2 promoter could slightly increase the photosynthesis and biomass yield of Synechocystis PCC 6803 7 . Only few studies have reported the use of Gro3P (glycerol-3-phosphate), a major product of the glpD-catalysed reaction, where Gro3P could ultimately flow to gluconeogenesis, glycolysis and lipid synthesis 9 . The strain overexpressing aas-_glpD_Rubisco (OAGR strain) gave the highest level of intracellular lipid accumulation of approximately 35.9% w/DCW at day 5 of cultivation ( Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the previous study suggested that overexpression of RuBisCO driven under psbA2 promoter could slightly increase the photosynthesis and biomass yield of Synechocystis PCC 6803 7 . Only few studies have reported the use of Gro3P (glycerol-3-phosphate), a major product of the glpD-catalysed reaction, where Gro3P could ultimately flow to gluconeogenesis, glycolysis and lipid synthesis 9 . The strain overexpressing aas-_glpD_Rubisco (OAGR strain) gave the highest level of intracellular lipid accumulation of approximately 35.9% w/DCW at day 5 of cultivation ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research revealed the enhancement of Gro3P synthesis, which enhanced lipid production in Synechocystis PCC6803, by introducing the heterologous GPD1 gene (encoding glycerol-3-phosphate dehydrogenase) from Saccharomyces cerevisiae and the atf1 gene (encoding diacylglycerol acyltransferase, DGAT) from the oleaginous bacterium Rhodococcus opacus PD630 9 . However, Gro3P also generally functions as a substrate for other pathways including starch and glycogen biosynthesis, isoprene and carotenoid synthesis [9][10][11][12] .…”
mentioning
confidence: 99%
“…PCC 6803 was improved by the expression of GPD1 from Saccharomyces serevisiae and DGAT from Rhodococcus opacus . These genes, which encode glycerol‐3‐phosphate dehydrogenase and diacylglycerol acyltransferase, are the key ones in the lipid metabolism of cyanobacteria …”
Section: Genetically Engineered Cyanobacteriamentioning
confidence: 99%
“…The carbon partitioning and product yields differ in various growth phases (Wang et al . ; Schuurmans et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…However, synthesis of foreign compounds has been shown to compete with natural carbon partitioning in growing cells (Schuurmans et al 2017;Giordano and Wang 2018). The carbon partitioning and product yields differ in various growth phases (Wang et al 2016;Schuurmans et al 2017). For instance, enhanced production is obtained by metabolically active cells in the absence of growth (Berla et al 2013).…”
Section: Introductionmentioning
confidence: 99%